Integrated Transcriptomic and Proteomic Analysis in the Roadmap of the Xylem Development Stage in Populus tomentosa - Zhang, Chong; Zhang, Jiaxue; Liu, Yadi; Liu, Xiatong; Guo, Xiaorui; Li, Hui; Liu, Di; Lu, Hai (Frontiers in Plant Science, 2021)
Xylem development plays an important role of wood formation in plants. In this study, we found that xylem was rapid thickening, including increased of the number and the thickness of secondary wall of tracheary elements (TE) and fiber cells, and then slowly increasing. Transcriptome ananlysis showed that xylan and lignin biosynthetic pathway, which involved in the early rapid thickening of the xylem, were mainly up-regulated in the second-month. 124 transcription factors, including 28 NAC TFs and 31 MYB TFs, were the highest expression level at WT-2M or WT-3M compared with WT-1M. Based on reported literature and key cis-acting elements SNBE, SMRE, W-box or TGTG[T/G/C], 10 transcription factors related to xylem development, 50 transcription factors with unknown function, 98 cell wall biosynthetic genes and 47 programmed cell death (PCD) genes were used to construct a transcriptional regulatory network of four-layered poplar NAC domain transcription factors–mediated for demonstrating the transcriptional regulation of cell wall biosynthesis and programmed cell death in Populus tomentosa. The proteome reveal that post-transcriptional modification may widely involve in lignification development. Taken together, our results reveal that xylem development is a rapid thickening process in Populus tomentosa, which has distinct time expression patterns from cell division to cell death.